Parton distribution functions and transverse momentum dependence of heavy mesons - Serna, Fernando E.; El-Bennich, Bruno [UNESP]; Krein, Gastão [UNESP] (American Physical Society (APS), 2024)
The leading Fock-state light-front wave functions of heavy quarkonia and D and B mesons are obtained from the projections of their Bethe-Salpeter wave functions on the light front. We compute their leading-twist time-reversal even transverse momentum distributions and parton distribution functions. Mirroring the behavior of parton distribution amplitudes, the support of both distributions is increasingly narrower and shifted toward larger x as a function of the meson mass. The dependence of x and k ⊥ 2 of the transverse distributions does not factorize into separate functions, and their falloff with k ⊥ 2 is much slower than that of light mesons. Published by the American Physical Society 2024